Superhydrophobic and Low Reflectance Carbon Nanotubes Buckypapers - Campos,Rodrigo Bezerra Vasconcelos (2022)
Abstract In this paper, carbon nanotube (CNT) buckypapers (BPs) were produced by vacuum filtration of CNT water suspensions prepared by sonication using 0.5 wt % of Triton X-100 dispersing agent. The as-produced BPs were efficiently dispersed and presented very low optical reflectance, with an average reflectance of 1.30% in the visible range and hydrophilic/oleophilic properties, readily absorbing water or oil liquid drops through their network of pores. Plasma treatment with 1, 1, 1, 2 tetrafluoroethane (C2H2F4) turned the BPs superhydrophobic with water contact angles (CA) greater than 140°, while still maintaining their oleophilic properties unchanged. This effect is attributed to the combination of the decrease of surface energy and modification of the surface structure with micro/nanopores due to the coating with a fluorocarbon film. After only 1 minute plasma treatment, the BPs presented high hydrophobicity (CA = 145°) while keeping their oleophilicity and the very low optical reflectance essentially unaffected. These results indicate that a good combination of low reflectance and a superhydrophobic/oleophilic behavior can be achieved which is of importance for technological applications that require super black surfaces and prevent water from being absorbed, improving the handling of optical signals and increasing the useful life of materials.